0252 The legacy of in situ asbestos cement roofs in south africa. (21st August 2017) - Rees, David; Phillips, James Ian
Abstract : In the 1970s, South Africa was the world's third largest producer of asbestos. The amphiboles, amosite and crocidolite, were mined in large quantities along with chrysotile. Most asbestos was exported but some was used locally to manufacture products including asbestos cement (AC)roof sheets which were used to build houses and schools. Although asbestos was banned in South Africa in 2008, there are over a million houses with AC roofs. Asbestos Regulations promulgated in 2002 prescribe the method for working with and demolishing asbestos containing materials and a key step is the identification of asbestos. The NIOH provides a national service to identify asbestos in materials and from 2003 to 2016, some 2657 samples have been analysed, including 155 roofs. Of these, 135 (87%) contained asbestos and 97 (72%) of the AC roofs contained amphibole asbestos fibres either alone or in a mixture. This suggests that several million people are living under a roof containing amphibole asbestos. Studies that sampled the air for asbestos fibres in a township built with AC roofs indicate that fibres are not normally liberated from the roofs. Another study in the same township has shown that over many years, asbestos can be leached from roofs by rainwater and fibres can be found in the soil below roofs which have no gutters. The legacy of AC roofs on homes and schools is a concern for residents and parents. The magnitude of the problem raises concerns about the safe removal, disposal and cost to replace these roofs.